Accelerating Mixture Design for Cement Treated Base Material. Issue 3 (March 2023) - Sebesta, Stephen; Kim, Jinho; Rew, Younho; Taylor, Ross; Townsend, Peter
The stabilization of roadway and stockpile materials enhances the strength and stiffness properties of pavement base layers, allowing those layers to meet structural requirements in a cost-effective and sustainable manner. Historically, mixture stabilization design criteria have relied on unconfined compressive strength (UCS) results and, depending on the treatment type and test methods, they can take nearly a month to complete. Additionally, different treatment types currently require different preparation, curing time, and acceptance criteria. This research develops a harmonized and accelerated design procedure for cement-treated base materials with the objective of producing acceptable mixture design recommendations. This work focuses on a rapid test turnaround time, the inclusion of moisture conditioning in the mix design, and performance-related design criteria by relating an accelerated-cure indirect tensile test (IDT) to UCS and modulus of rupture (MoR). The resulting strength relationship model for the MoR, UCS, and IDT was found to show promise for estimating UCS based on an accelerated-cure IDT, and potentially estimating MoR from that same IDT. The newly formulated IDT test method illustrates the possibility of accelerating the mixture design procedure for cement-treated bases and harmonizing with mix design procedures used for emulsion and foamed asphalt-treated base materials.